2017
DOI: 10.5114/bta.2017.68309
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline trypsin from the viscera and heads of Engraulis anchoita : partial purification and characterization

Abstract: Marine by-products contain valuable protein fractions. To ensure a profitable utilization of wastes from the fish industry, the knowledge about their quality and composition is necessary. Fish digestive proteolytic enzymes from cold-adapted ectothermic organisms have found applications in several industries because their temperature requirements and other characteristics differ from those of homologous proteases from warm-blooded animals. Herein, we describe detection, partial purification, and characterizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…The use of fish waste as source of proteolytic enzymes and collagen is an emerging field of research. In Argentina previous works only included alkaline proteases studies from Engraulis anchoita (Lamas, Yaennes, & Massa, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The use of fish waste as source of proteolytic enzymes and collagen is an emerging field of research. In Argentina previous works only included alkaline proteases studies from Engraulis anchoita (Lamas, Yaennes, & Massa, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Engraulis anchoita (Lamas et al, 2017) have been studied for detergent formula. These enzymes were stable at 30 and 40 C for 1 h and kept high percentages of their initial activity in the presence of different commercial detergents such as Axion, New Det, Dixan and Ariel.…”
Section: Discussionmentioning
confidence: 99%
“…Although the activity of digestive enzymes of various fish species such as Sardinops sagax caerulea (Castillo-Yañez et al, 2004), Sardinella aurita (Khaled et al, 2011), Salaria basilisca (Ktari et al, 2012), Pangasianodon gigas (Vannabun et al, 2014), Raja Clavata (Lassoued et al, 2015), Liza aurata (Bkhairia et al, 2016), Scomberomorus guttatus (Rengasamy et al, 2016), Seriola dumerili (Oliveira et al, 2017), Prochilodus lineatus (Gomez et al, 2018), Sardinella longiceps (Ramkumar et al, 2018) and Bagre panamensis (Rios-Herrera et al, 2019) have been extensively reported, a small number of researchers have focused on the digestive enzymes of Argentine marine fish species. In this sense, only trypsin from the viscera and heads of M. hubbsi (Lamas et al, 2015) and Engraulis anchoita (Lamas et al, 2017) have been characterized.…”
Section: P Brasiliensis C Guatucupa and Brazilian Codling Urophycis Brasiliensismentioning
confidence: 99%
“…This Km value was much lower than protease enzymes isolated from brown stripe red snapper (Lutjanus vitta) with the value of 0.507 mM for α-N-benzoyl-DL-arginine-q-nitroanilide (BAPNA) and 0.328 mM for α-N-ρ-tosyl-L-arginine methyl ester (TAME) as a substrate (Khantaphant and Benjakul, 2010). Further research on protease from viscera and heads of Engraulis anchoita also suggested that BAPNA was more favourable than that of casein (Lamas et al, 2017).…”
Section: Enzyme Kineticsmentioning
confidence: 99%